(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2014)
One view of consciousness that has long appealed to aminority of philosophers and cognitive scientists is to view the brain like aradio or television set. These appliances emit sound and/or visual imagery, butof course the information presented in the sounds and sights is not determinedby components within the device itself. The information is carried withinelectromagnetic waves. A radio or TV is simply equipped to transduce thisenergy into sound or images. In the same way, according to this minority view,the brain does not produce consciousness through its activity, but acts as akind of receiver of signals from outside the brain that are the real source ofconsciousness. There is as yet no evidence for any kind of consciousness field,analogous to an electromagnetic field that could act as the source of ourbrain-derived experience of consciousness. But my point here is that, properlyunderstood, individual human consciousness results from a process not that muchunlike that underlying radio or television. Rather than a field ofconsciousness that can exist independently of individual humans, there is asocial consciousness that is created by interactions between individuals, inlarge part through language. The individual brain is able to transduce thissocial consciousness into an individual form of consciousness.